Status of insecticide resistance in rice brown planthopper (Nilaparvata lugens) in Punjab - DEOSI, KIRANDEEP KAUR; SURI, K S (The Indian Journal of Agricultural Sciences, 2022)
The present study was undertaken in 2017–18 at the entomological Research Farm, PAU, Ludhiana to determine the status of insecticide resistance and the role of enzymes in imparting resistance in Nilaparvata lugens. Toxicity of insecticides, viz. imidacloprid, chlorpyriphos, quinalphos, buprofezin and lambda cyhalothrin against the susceptible and field populations of N. lugens were evaluated. Based on LC50 values calculated, the susceptible population showed the highest sensitivity to buprofezin with lowest LC50 value of 0.0007% while the lowest sensitivity was observed for chlorpyriphos (0.0010%). Buprofezin proved most effective against planthopper population collected from Ludhiana and Patiala with LC50 values of 0.0032% and 0.0036% and toxicity ratios of 4.40 and 2.75, respectively, whereas quinalphos proved effective against Kapurthala population with LC50 value of 0.0027% and toxicity ratio of 2.85. Imidacloprid was the least effective insecticide at all test locations (LC50 values ranged from 0.0077% to 0.0141%). N. lugens population showed moderate level of resistance development to imidacloprid at all the test locations, viz. 19.09-folds in Ludhiana, 14.14-folds in Patiala and 11-folds resistance in Kapurthala. The resistance ratio for buprofezin was the lowest (4.57-folds) in case of Ludhiana population, whereas in case of Patiala and Kapurthala populations, resistance to quinalphos was the lowest (4.39 and 3.00-folds, respectively). The activity of esterases was significantly higher in the field populations collected from Ludhiana whereas the activities of acetylcholinesterase in resistant populations of Ludhiana and Patiala were significantly higher than in the susceptible population, indicating their probable role in imparting resistance.